2017
DOI: 10.1080/15284336.2017.1404690
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and severity of potential drug interactions in a cohort of HIV-infected patients Identified through a Multidisciplinary team

Abstract: Systematic evaluation detected a significant percentage of PDDIs requiring an intervention in HIV patients on ART. Monitoring and advice about drug-drug interactions should be part of routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“… reported red DDIs mostly for nevirapine in combination with ketoconazole in their cohort in Uganda. Other studies in Switzerland and Spain reported mainly on red interactions between protease inhibitors/NNRTIs and central nervous system drugs or proton‐pump inhibitors . These drug categories were rarely prescribed in our cohort.…”
Section: Discussionmentioning
confidence: 82%
“… reported red DDIs mostly for nevirapine in combination with ketoconazole in their cohort in Uganda. Other studies in Switzerland and Spain reported mainly on red interactions between protease inhibitors/NNRTIs and central nervous system drugs or proton‐pump inhibitors . These drug categories were rarely prescribed in our cohort.…”
Section: Discussionmentioning
confidence: 82%
“…HIV/HCV coinfection, age, the prescribed antiretroviral regimen, and polypharmacy are independent risk factors for DDIs (45,46). It is therefore unsurprising that the prevalence of clinically relevant DDIs ranges from 14 to 41% (9,45,47).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between ARVs and concomitant medications has been reported at rates of 14-41% [3] . Drug-drug interaction is common in HIV-infected patients because these drugs act as drug metabolism enzyme inducers or inhibitors.…”
mentioning
confidence: 99%
“…Therefore, it is important to consider potential interactions to ensure effective viral suppression and minimal toxicity. It was reported that 70% of the 1.259 HIV-infected patients in Spain (from March 2015 to September 2016) used co-medications, and drug-drug interactions occured in 44.7% [3] . In this paper, we present the development of an unexpected drug-drug interaction in a patient starting ART and how it was managed.…”
mentioning
confidence: 99%
See 1 more Smart Citation